After Translation : The Transfer and Circulation of Modern Poetics Across the Atlantic - Infante, Ignacio (Book collections on Project MUSE., 2013)
Translation - from both a theoretical and practical point of view - articulates differing but interconnected modes of circulation in the work of writers originally from different geographical areas of transatlantic encounter, such as Europe, Latin America, North America, and the Caribbean. This book examines from a transnational perspective the various ways in which translation facilitates the circulation of modern poetry and poetics across the Atlantic.